PENERAPAN AROMATERAPI SEREH TERHADAP KECEMASAN MENGHADAPI PERSALINAN PADA NY D DI PUSKESMAS TANJUNG BALAI KARIMUN - Nilma; Mariyana; Roza, Nova (Universitas Batam, 2024)
Anxiety about childbirth is felt by all pregnant women before delivery. Essential oils in labor can improve coping strategies in birthing mothers. The main role of essential oils during labor and delivery is to help relieve pain, stress and anxiety. The aim is to provide midwifery care for mothers in a comprehensive and sustainable manner, with management of midwifery care in accordance with midwifery service standards. Midwifery care that is applied is the application of citronella aromatherapy to anxiety in facing childbirth. The practice report preparation method is descriptive research with the case study method conducted at the Tanjung Balai Karimun Health Center in February 2023. The subject used in this case study with midwifery care management was Mrs. D. Results and Conclusions Evaluation of the care provided related to the application of lemongrass aromatherapy to the anxiety of facing childbirth there is a reduction in the anxiety that the mother feels